Key factor of environmental pollution of the domestic solid waste in the city of Derna, Libya - Jumma Arhouma Jumma; Mohd Ekhwan Toriman; Noorazuan Md Hashim (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2009)
The study aims to identify the most important reasons that led to the aggravation of the problem, the resulted consequences and the methods used in the city to dispose it. A minimum sample of 370 families was used and distributed for them questionnaire using the Stratified Relatively Sample. Chi Square was employed to analyze the statistical data and converted them into tables, percentages and graphics. The environmental awareness of citizens and methods of getting rid of the domestic garbage are playing an effective role in limiting the size of the resulting garbage problem. Where, 41.1% of the families save the garbage in plastic bags, and this is Ineffective way, and 39% of them do not commit to the specific times of removing the garbage. The apparent lacks of mechanisms, equipments and labors used in the process of cleaning in the Environment Protection Agency have led to the increase of the problem in the city. This is resulted from the lack of financial resources. Besides that, 41.6% of residents throw the waste in open places, and remain stacked for long periods in the streets and open areas in the city. Even after the process of the collection it gets disposed in an open dunghill within the border of the city and is sometimes burned, which would generate the spread of odors and distort the environmental view and standards as well as the proliferation of stranded roaming animals, rodents and insects which causes and transfers diseases.